Effects of intravenous nitroglycerin on left ventricular function and ST segment changes in acute myocardial infarction. Issue 6 (June 1976) - Flaherty, J T; Come, P C; Baird, M G; Rouleau, J; Taylor, D R; Weisteldt, M L; Greene, H L; Becker, L C; Pitt, B
Abstract : It has been shown previously that 30-minute infusions of intravenous nitroglycerin in patients with acute myocardial infarction are able to lower left ventricular filling pressure and improve left ventricular function while lowering mean arterial pressure by only 7 mmHg (0.9 kPa). A decrease in sigmaST in praecordial ST segment mapping studies during nitroglycerin infusion in patients with anterior infarction suggested a decrease in the extent of myocardial ischaemia. In the present study, 30 patients with acute myocardial infarction received 1- to 3-hour infusions of intravenous nitroglycerin at infusion rates sufficient to lower mean arterial pressure by an average of 22 mmHg (2.9 kPa). An improvement in ventricular function was noted in that subgroup of patients with the msot severe left ventricular dysfunction. All patients with anterior myocardial infarction underwent serial ST segment mapping and, irrespective of the presence or absence of left ventricular failure, showed a decrease in sigmaST during nitroglycerin infusion (P less than 0.005). These findings suggest that infusion of nitroglycerin improves left ventricular function and/or alters left ventricular compliance in patients with left ventricular failure complicating myocardial infarction and furthermore decreases sigmaST in all patients, irrespective of the presence or absence of left ventricular failure, suggesting that the extent of myocardial ischaemia is decreased.